2019
DOI: 10.1080/15309576.2019.1676275
|View full text |Cite
|
Sign up to set email alerts
|

Police Performance As Symbolic Politics? Public Recognition and the Value of Awards

Abstract: What constitutes "good" performance in a law enforcement agency, who decides, and how does public recognition of that performance change how an agency performs? This study uses a quasiexperimental design and propensity-score matching model to assess the impact of a law enforcement agency's status as a finalist for the annual Cisco/International Chiefs of Police Association (IACP) Community Policing Award on performance in future years, as measured by crime clearance rates. It is found that after comparing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 112 publications
0
8
0
Order By: Relevance
“…In order to understand the performance of policing in a community, it is better to understand the idea of community policing and its operations. Community policing dates back to 1980s and originated from some cities in United States of America such as Los Angeles and New York (Federman 2020 ; Weisburd and Braga 2006 ). Generally, it is the expectation of community members that the police maintain peace and order and attend to broad range of criminal and trouble situations in ensuring peace and orderliness (Sitorus 2019 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to understand the performance of policing in a community, it is better to understand the idea of community policing and its operations. Community policing dates back to 1980s and originated from some cities in United States of America such as Los Angeles and New York (Federman 2020 ; Weisburd and Braga 2006 ). Generally, it is the expectation of community members that the police maintain peace and order and attend to broad range of criminal and trouble situations in ensuring peace and orderliness (Sitorus 2019 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The performance of police officers is measured by the members of a community through the rate of crime clearance. Good performance of the police is based on the community recognition of how the police deals with criminal matters as perceived by the people (Federman 2020 ; Kaariainen 2008 ). The outcome of a qualitative study of a community in Australia revealed that depending on how the police conduct themselves during an encounter between the police acting to secure the legitimacy of their operation, and the public seeking procedural justice enhance the trust that the people in the community have in the police (Schermuly 2018 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Much of this research considers the distribution of public services, determination of best practices, and the gatekeeping of services depending on particular organizational factors. It includes questions that consider how citizens interact with e-governance tools, how awards and best practices in public service are given and distributed, the use of discretion among street-level bureaucrats, and how racial representation can impact the citizen–government relationship (Federman, 2019; Harrits & Møller, 2014; Jakobsen et al, 2019; Thomas & Streib, 2003; Watkins-Hayes, 2011). However, many of these interactions are the result of citizen-initiated contact, based upon the desire of a citizen to have contact with their government, or viewed through an organizational lens, with a focus on organizational outcomes for a given agency.…”
Section: Citizen–police Interactionsmentioning
confidence: 99%
“…We investigate whether offering positive recognition to elected, local leaders who manage public funds with integrity strengthens anti-corruption norms among leaders and the public, and improves the administration of public projects. While awards are becoming a larger part of public administration (Hatry, 2010;Federman, 2020), there is limited empirical evidence about whether they can promote integrity and decrease corruption. We provide one of the first research designs that yields causal evidence.…”
Section: Introductionmentioning
confidence: 99%